The first evidence of osteomyelitis in a sauropod dinosaur. (30th September 2016) - García, Rodolfo A.; Cerda, Ignacio A.; Heller, Matías; Rothschild, Bruce M.; Zurriaguz, Virginia
Abstract : Osteomyelitis is reported for the first time in a sauropod dinosaur. The material (MCS‐PV 183) comes from the Anacleto Formation (Campanian, Late Cretaceous), at the Cinco Saltos locality, Río Negro Province, Argentina. The specimen consists of 16 mid and mid‐distal caudal vertebrae of a titanosaur sauropod. Evidence of bacterial infection is preserved in all of these vertebrae. The main anomalies are as follows: irregular 'microbubbly' texture of bone surfaces produced by periosteal reactive bone, abscesses on the rims of the anterior articular surfaces of two centra, numerous pits on centra anterior articulation surfaces, erosions on the anterior articulation of the vertebral centra, a vertical groove in posterior articular face of all the centra and disruption of the prezygapophysis and postzygapophysis (mainly the articular face) from the vertebra 19 and beyond. The last anomaly is increasingly pronounced in more distal elements of the series. Thin sections reveal that the anomalous cortical tissue is composed of avascular and highly fibrous bone matrix. The fibres of the bone matrix are organized into thick bundles oriented in different directions. Both morphological and histological abnormalities in the MCS‐PV 183 specimen are pathognomonic for osteomyelitis.